2021
DOI: 10.2991/assehr.k.211209.013
|View full text |Cite
|
Sign up to set email alerts
|

Does Institutional Investor Ownership Influence Corporate Cash Holding?

Abstract: Based on a sample of Shenzhen and Shanghai Exchange in 2007-2017, this paper examines the effect of institutional investor ownership on corporate cash holding. We establish the fixed effects model to study the relationship between them, and we use robustness checks and derive our results also have the robustness. Moreover, we do the heterogeneity analysis and find the impact of institutional investor ownership on corporate cash holding is more pronounced in firms with non-state-owned and non-Big 4 auditings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Hypothesis 1: the value of cash holdings is higher in Shariah-compliant firm According to Jiang et al [20], their research shows that active institutional investors increase the level of cash holdings in companies. Previous studies have also demonstrated that institutional investors are better at utilizing current information and making more accurate predictions of future earnings compared to non-institutional investors [21].…”
Section: Hypothesesmentioning
confidence: 99%
“…Hypothesis 1: the value of cash holdings is higher in Shariah-compliant firm According to Jiang et al [20], their research shows that active institutional investors increase the level of cash holdings in companies. Previous studies have also demonstrated that institutional investors are better at utilizing current information and making more accurate predictions of future earnings compared to non-institutional investors [21].…”
Section: Hypothesesmentioning
confidence: 99%
“…Because the ability to acquire debt may be used as a proxy for a firm's cash needs, high leverage results in a decline in corporate cash holdings. [27]. Based on a sample of Shenzhen and Shanghai exchange in 2007-2017, Jiang and Li point out that institutional investors can collect complete information and therefore their prudence may be higher.…”
Section: The Promotion Effectmentioning
confidence: 99%